Nutrient Value and In Vitro Digestibility of Pennisetum purpureum cv. Mott under Varying Gamma Irradiation Doses in Acidic Soil - Putra, B.; Gopar, R. A.; Surachman, M.; Darmawan, I. W. A.; Maulana, S.; Prasetya, B. (Tropical Animal Science Journal, 2024)
Gamma irradiation is an emerging technique in agriculture with the potential to enhance the nutritional quality of forage crops and improve their adaptability to infertile environments. This study examined how different doses of gamma irradiation affected the nutrient content, calcium (Ca) and phosphorus (P) uptakes, and the in vitro digestibility of Pennisetum purpureum cv. Mott, a forage grass cultivated on acidic soil. The experiment involved the application of various gamma irradiation doses (0 Gy, 5 Gy, 10 Gy, 15 Gy, 20 Gy, 25 Gy, and 30 Gy). Four replications were done using a randomized block design, with 25 P. purpureum cv. Mott seeds in each repetition, totaling 700 seeds. The plants were grown in acidic soil with a pH of approximately 4.5–5. After two months of growth, the plants were harvested, and various parameters were analyzed. The research results indicated that the treatment had a significant effect on increasing organic matter content (p<0.01), NDF (neutral detergent fiber) (p<0.01), ADF (acid detergent fiber) (p<0.01), cellulose (p<0.01), hemicellulose (p<0.01), crude protein (p<0.01), crude fat (p<0.05), non-nitrogen-free extract (p<0.05), fiber fractions (p<0.01), nutrient digestibility (p<0.01), and fiber fraction digestibility (p<0.01). Overall, it can be concluded from this study that a gamma irradiation dose of 15 gy can enhance the nutritional content of P. purpureum cv. Mott cultivated on acidic soil and improves its utilization efficiency for livestock due to the increased digestibility.